The African disability scooter: efficiency testing in paediatric amputees in Malawi. (2nd April 2016) - Beckles, Verona; McCahill, Jennifer L.; Stebbins, Julie; Mkandawire, Nyengo; Church, John C. T.; Lavy, Chris
Abstract: Purpose : The African Disability Scooter (ADS) was developed for lower limb amputees, to improve mobility and provide access to different terrains. The aim of this study was to test the efficiency of the ADS in Africa over different terrains. Method : Eight subjects with a mean age of 12 years participated. Energy expenditure and speed were calculated over different terrains using the ADS, a prosthetic limb, and crutches. Repeated testing was completed on different days to assess learning effect. Results : Speed was significantly faster with the ADS on a level surface compared to crutch walking. This difference was maintained when using the scooter on rough terrain. Oxygen cost was halved with the scooter on level ground compared to crutch walking. There were no significant differences in oxygen consumption or heart rate. There were significant differences in oxygen cost and speed between days using the scooter over level ground, suggesting the presence of a learning effect. Conclusions : This study demonstrates that the ADS is faster and more energy efficient than crutch walking in young individuals with amputations, and should be considered as an alternative to a prosthesis where this is not available. The presence of a learning effect suggests supervision and training is required when the scooter is first issued. Implications for Rehabilitation: The African Disability Scooter: is faster than crutch walking in amputees; is more energy efficient than walking with crutches; supervised use is needed when learning to use the device; is a good alternative/adjunct for mobility.